2023
DOI: 10.3390/agronomy13071774
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Influence of Applying Two Culture Filtrates to Control Gray Mold Disease (Botrytis cinerea) in Tomato

Abstract: Botrytis cinerea, a causal agent of gray mold disease, is one of the most destructive fungal pathogens that leads to substantial global economic crop losses, especially for tomato plants. The present study aims to investigate the inhibitory effect of two microbial culture filtrates (BCA filtrate alone and combined with salicylic acid) of Trichoderma longibrachiatum and Pseudomonas sp. against the phytopathogenic fungus B. cinerea on tomato plants. The biochemical modifications, gray mold disease incidence, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Biocontrol experiments against B. cinerea have been attempted by the biological control agents which are most commonly filamentous fungi from the genera Trichoderma (Herrera-Téllez et al, 2019 andNawrocka et al, 2023), Ulocladium and Gliocladium (Sarven et al, 2020), bacteria from the genera Bacillus (Zhou et al, 2021) and Pseudomonas (Hajji-Hedfi et al, 2023) and yeasts from the genera Pichia and Candida (Kasfiet al, 2018) under laboratory, fields and greenhouse conditions (Herrera-Téllez et al, 2019 andNawrocka et al, 2023). Hajji-Hedfi et al, (2023) found that disease severity in tomato seedlings and fruits was significantly reduced when treated with Trichoderma sp. and Pseudomonas sp.…”
Section: Disease Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Biocontrol experiments against B. cinerea have been attempted by the biological control agents which are most commonly filamentous fungi from the genera Trichoderma (Herrera-Téllez et al, 2019 andNawrocka et al, 2023), Ulocladium and Gliocladium (Sarven et al, 2020), bacteria from the genera Bacillus (Zhou et al, 2021) and Pseudomonas (Hajji-Hedfi et al, 2023) and yeasts from the genera Pichia and Candida (Kasfiet al, 2018) under laboratory, fields and greenhouse conditions (Herrera-Téllez et al, 2019 andNawrocka et al, 2023). Hajji-Hedfi et al, (2023) found that disease severity in tomato seedlings and fruits was significantly reduced when treated with Trichoderma sp. and Pseudomonas sp.…”
Section: Disease Managementmentioning
confidence: 99%
“…and Pseudomonas sp. Furthermore, the combined treatment with Trichoderma sp., Pseudomonas sp., and salicylic acid-induced significant biochemical and physiological changes in fruit and seedlings (Hajji-Hedfi et al, 2023).…”
Section: Disease Managementmentioning
confidence: 99%
“…Yet, these fungicides have not shown satisfactory efficacy since V. dahliae aptitude to survive in the setting for a long time and to spread readily by way of various agricultural applications (Montes-Osuna & Mercado-Blanco, 2020;Ziazia et al, 2021). Hence, the possible dangers complicated in applying phytochemicals to olive trees for both the location and social health, composed of their narrow efficacy for controlling Verticillium-induced diseases, funding the want to find alternatives to trade their use or expand their ability (Hajji-Hedfi et al, 2023a;Rhouma et al, 2023a).…”
Section: Management Of Verticillium Wilt On Olive Treementioning
confidence: 99%
“…The use of resistant cultivars is prudent since it is an ecologically friendly (Rhouma et al, 2023a), and green manipulation for the Verticillium wilt of olive, as well as efforts to look for new genotypes and/or examine to be had cultivars have been reviewed. Santos-Rufo et al (2023), andMarkakis et al (2022) found that 'Atsiholou', 'Koroneiki', 'Frantoio', and 'Tragolia' represent the most resistant varieties to Verticillium wilt in olive trees.…”
Section: Management Of Verticillium Wilt On Olive Treementioning
confidence: 99%
“…The rapidity with which the disease spreads makes it very difficult to follow only chemical control (Liu et al 2016) which has many risks including hazardous effects on human and animal health, effects on nontarget organisms, the entrance of residual toxic compounds in the food chain and effects on microorganism biodiversity (Rhouma et al 2021e;Hajji-Hedfi et al 2022;Hajji-Hedfi et al 2023). Therefore, the researchers developed many programs to control plant diseases by using eco-friendly biopesticides which contain biological control agents like arbuscular mycorrhiza, endophytic fungi (Trichoderma spp., Chaetomium spp., Gliocladium spp., Paecilomyces spp., Acremonium spp., Beauveria spp., etc.)…”
Section: Disease Managementmentioning
confidence: 99%